A Learning Approach: Individual Differences in Teaching and Learning Languages through Literature Review - Aisiah, Sitti; Puspitasari, Eka; Amaluddin, Amaluddin (Edumaspul: Jurnal Pendidikan, 2024)
Language learning and teaching involves the acquisition and instruction of language skills. However, not all learners approach language learning in the same way, and individual differences play an important role in the effectiveness of the language learning and teaching process. This study aims at how to understand individual differences in language learning and teaching for educators as this allows them to adjust their instructional strategies to meet the needs of diverse students.This research method is qualitative which is taking references from books or from articles that these works provide valuable insights into individual differences and their impact on language learning, The results showed that there are several Affective factors that influence individual differences in the acceptance of language learning and teaching such as Learning Styles, Cognitive Abilities, Personality Traits, Motivation and Goal Orientation, Age and Language Learning, Linguistic Background, Cultural Influences, Language Anxiety, Learning Disabilities and Special Needs, Technology and Digital Literacy, Feedback and Individualized Assessment, Implications for Classroom Practice, Case Studies as a examples and create a more effective and engaging language learning environment. By addressing individual differences, teachers can better support students in their language learning journey and promote positive learning outcomes. In addition, considering individual differences fosters a sense of inclusiveness, appreciates students’ unique strengths and challenges, and encourages a student-centered approach to language teaching.